In vitro fertilization and age. When old is too old? - Pokulniewicz, Marek; Issat, Tadeusz; Jakimiuk, Artur (Menopause Review/Przegląd Menopauzalny, 2015)
This case report refers to a 53-year-old female patient who deliberately misinformed the staff of the In vitro fertilization (IVF) clinic using counterfeit documents concerning her real age and underwent the IVF procedure. During the pregnancy it was discovered accidentally that the patient was not telling the whole truth about her real age. In the 34th week of pregnancy two healthy twins have been delivered by a cesarean section. Somehow the trust between the patient and the doctor was compromised, however we can acknowledge this case of postmenopause pregnancy as a therapeutical success for the clinic and for the patient herself. The mother invested her time, emotions and financial resources, and risked her health undergoing IVF procedures and carrying the pregnancy to fulfill her wish and deliver a child. Regardless of her intentions, we can argue about her knowledge concerning this procedure and awareness of threats to pregnancy resulting from her age. The age of childbearing in Western societies has been considerably delayed nowadays, mainly because of social aspects. Many institutions nowadays try to face these aspects, which produces certain medical issues. In this case report authors also present literature review on age and pregnancy after IVF.